(untitled) (Scientific journal of the Fergana State University, 2025)
A new metallocomplex compound containing [Cu(2-OHnaph)2H2O] was synthesized from the interaction of solutions of 2-hydroxy 1-naphthaldehyde (2-OHnaph) with CuSO4 in ethyl alcohol. The composition, molecular and crystal structures of this metallocomplex compound were investigated using differential scanning calorimetry (DSC), IR-spectrum and X-ray structure analysis (XRSA). It was found that the thermal decomposition of the organic part of the metal complex in the DSC-analysis is different, starting from 115°C and ending in the temperature range of 370°C. The data obtained in the XRSA analysis also proved the presence of coordination water molecules. Based on the obtained data, the Hirshfeld surface analysis of the complex was studied. The results of the surface analysis revealed that the main part of the effects are H...O/O...H, H...H and H...C/C...H interactions that contribute the most to the Hirshfeld surface . The complex contains H…C/C…H (45.3%), H…H (34.7%) and H…O/O…H (11.8%), which is expected for molecules dominated by oxygen atoms.